Philosophical Influences on the Austrian School of Economics - Marguč, Karmen (Naše gospodarstvo/Our economy, 2014)
The fundamental idea of the subjectivist Austrian school of economics can be understood by recognizing philosophical influences that have made a significant con- tribution to the development of leading ideas. Due to the limited literature in this area, the need for research includes both a general overview of philosophical influ- ences and an analytical study of possible interactions. The results of this study have shown that the Austrian school was influenced by many philosophers, such as Aristotle, Brentano, and Weber, as well as its own critical orientation against logical positivists. The underlying fundamentals remain faithful to the basic principles of Men- ger. As such, it is interesting for further, more analytical study.